tách ra hằng đẳng thức thứ...-2^3-2^3 -1
= ( x+2 ) ^ 3 -9 còn lại tự nha
B=x+6x^2+12x+8-9
=(x+2)^2-9
Vì(x+2)^2\(\ge\)0=>(x+2)^2-9\(\ge\)-9
Dấu = xảy ra <=>x+2=0
<=>x=-2
Vậy MinB=-9<=>x=-2
\(B=x^3+6x^2+12x-1\)
\(B=\left(x^3+6x^2+12x+8\right)-9\)
\(B=\left(x+2\right)^3-9\)
\(B=\left(x+2\right)\left(x+2\right)^2-9\ge-9\)
Dấu "=" xảy ra \(\Leftrightarrow\)\(\left(x+2\right)^2=0\)
\(\Leftrightarrow\)\(x=-2\)
Vậy GTNN của \(B\) là \(-9\) khi \(x=-2\)
Chúc bạn học tốt ~
\(B=x^3+6x^2+12x-1\)
\(=x^3+3x^22+3x.2^2 +2^3-1-2^3\)
\(=\left(x+2\right)^3-8-1\)
\(=\left(x+2\right)^3-9\)
\(\left(x+2\right)^3\ge0\)
\(\Rightarrow\left(x+2\right)^3-9\ge-9\)
Dấu "=" xảy ra <=> x=-2
Vậy để B đạt Min khi x=-2